Developing a common law of animal welfare: offences against animals and offences against persons compared - Calley, Darren S. (Crime, law and social change, 2011)
Most animal welfare/suffering cases heard by the courts focus only on the facts: did the defendant, as a matter of fact, do those things with which they are charged? Analysis of the 2010 Amersham horse cruelty case reveals that there is significant room for ambiguity and subjective interpretation within the statutes that underpin animal welfare law. To provide certainty and to allow the law to develop it is essential that cases such as Amersham are not only subject to a review of the facts, but also a full analysis of the legal principles contained within the relevant statutes.